2014
DOI: 10.5430/jnep.v4n7p139
|View full text |Cite
|
Sign up to set email alerts
|

Conduct and utilization of research among nurses at federal capital territory, Abuja Nigeria

Abstract: Background: The need to support nursing practice with evidence and the demand for quality care have implications for conduct of research by nurses for nursing. Research findings are required to determine or establish evidence for practice. This study assessed how nurses conduct and utilize research. Methods: A cross sectional survey design was utilized to explore registered nurses' conduct and utilization of research. A structured questionnaire was distributed to 325 nurses from various health care institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 10 publications
4
19
0
Order By: Relevance
“…Previous studies investigating EBP in nursing in Nigeria have focused on individual determinants, utilising self-reported surveys as well as other quantitative approaches. [34][35][36][37][38][39][40] These studies focused on nurses' perceptions of barriers and facilitators of EBP as well as research utilisation using a quantitative approach.…”
Section: Limitations and Strengths Of The Studymentioning
confidence: 99%
“…Previous studies investigating EBP in nursing in Nigeria have focused on individual determinants, utilising self-reported surveys as well as other quantitative approaches. [34][35][36][37][38][39][40] These studies focused on nurses' perceptions of barriers and facilitators of EBP as well as research utilisation using a quantitative approach.…”
Section: Limitations and Strengths Of The Studymentioning
confidence: 99%
“…Several studies on the factors that hinder nurses' participation and utilization of research identified lack of time on the job, lack of knowledge, lack of funding, nurses poor attitude/perception towards research and lack of research support services as the key constraints [ 7 , 8 , 10 - 14 ]. Some studies within this field have been carried out in Nigeria [ 13 , 14 ], but little is known about clinical nurses' involvement in research, in Ghana. In addition, despite some efforts by the Nursing and Midwifery Council of Ghana, very little is seen from graduates of the various nursing programs working in clinical settings regarding clinical research.…”
Section: Introductionmentioning
confidence: 99%
“…[4,29,30,31] Even though the nurses agree that research is beneficial, important and advances nursing care practices, unfortunately majority of the nurses that have been involved in research in Nigeria are data collectors, coordinators of research being done by medical doctors and other professionals in the health care sector or to fulfill a degree requirement. [4,32] A recent study of conduct and utilization of research among nurses showed that out of 325 nurses, a few (21.2%) had conducted a research and 31.4% had utilized research findings in clinical practice. [32] Furthermore, it is difficult to ascertain the number of nurses involved in academic research in Nigeria due in part to the lack of records of national documentation of nurse researchers and the studies they have conducted.…”
Section: Nurses' Perception Involvement Utilization and Barriers Tomentioning
confidence: 99%
“…[4,32] A recent study of conduct and utilization of research among nurses showed that out of 325 nurses, a few (21.2%) had conducted a research and 31.4% had utilized research findings in clinical practice. [32] Furthermore, it is difficult to ascertain the number of nurses involved in academic research in Nigeria due in part to the lack of records of national documentation of nurse researchers and the studies they have conducted. [4] However, the positive perception of nurses and their awareness of the meaning and importance of nursing research indicate that although Nigerian nurses are limitedly involved in nursing research, a high percentage of them are desirous of being involved in nursing research if equipped with the right skills.…”
Section: Nurses' Perception Involvement Utilization and Barriers Tomentioning
confidence: 99%
See 1 more Smart Citation